Intrathecal Drug Delivery Systems for Refractory Pancreatic Cancer Pain: Observational Follow-up Study Over an 11-Year Period in a Comprehensive Cancer Center. (June 2018) - Carvajal, Gabriel; Dupoiron, Denis; Seegers, Valerie; Lebrec, Nathalie; Boré, François; Dubois, Pierre-Yves; Leblanc, Damien; Delorme, Thierry; Jubier-Hamon, Sabrina
Abstract : BACKGROUND: Pancreatic cancer is the fourth leading cause of cancer-related death in Europe and the United States. Studies have demonstrated that patients with pancreatic cancer have a high prevalence of pain, with rates varying from 47% to 82%. Analgesia using intrathecal drug delivery systems (IDDS) has been poorly studied specifically in this population. METHODS: The IDDS for pancreatic cancer pain was a follow-up observational study designed to evaluate 11-year results of IDDS for refractory pancreatic cancer pain at the Institut de Cancérologie de L'Ouest, Paul Papin in France. Patients were followed from March 2006 to April 2017. Patients were selected for IDDS based on multidisciplinary meeting discussion. All IDDS-treated patients were prescribed a combined intrathecal analgesics regimen through a catheter placed according to painful metameric level. Postimplant assessment of pain was determined using a numerical rating scale (NRS). Patients were followed via day-hospital visits and telephone calls at least monthly until death. Pain scores were compared using the Wilcoxon signed rank test. Overall survival (OS) was estimated using the Kaplan–Meier method and compared between groups by log rank tests. RESULTS: Ninety-three patients received IDDS, and total therapy duration accounts for 10, 300 IDDS days. Implanted patients suffered from severe pain before implantation (median presurgical NRS, 8 [interquartile range, 7–9]) despite a median 360 mg (260–600) oral morphine equivalent daily dose. Median OS in the whole cohort after intrathecal treatment start was 82 days (95% confidence interval, 59–95). Median OS after surgery for implantable pump was 91 days (83–111) and for external pump 27 days (20–49; P < .0001). IDDS was associated with pain relief with a significant statistical difference between preimplantation NRS pain score and 1 week (median, −6 [−7 to −4]; P < .001), 1 month (median, −5 [−6 to −3]; P < .001), and 3 months (median, −6 [−7 to −4]; P < .001). Severe pain (NRS score, ≥7) decreased from 89.2% before surgery to 4.5% after 1 week, 6.7% after 1 month, and 10.3% after 3 months of IDDS implant ( P < .01). Global complications rate was low, consistent with published literature. CONCLUSIONS: Despite our study's limitations, results suggest that long-term IDDS for refractory malignant pain due to pancreatic cancer was both efficacious and safe in pancreatic cancer pain. We have demonstrated, in the largest series of IDDS for pancreatic cancer pain reported yet, a clinically and statistically significant pain reduction in patients receiving IDDS.